Policy Hybridization: Continuity and Change in Swedish Research Funding - Cocos, Marta (Scandinavian Journal of Public Administration, 2020)
This paper follows recent calls to focus on how policy hybridity is formed using a research policy case, an area that has undergone profound changes in the last four decades. More specifically, it focuses on the case of Swedish research funding and its major institutional reorganization in 2000. Following the argument that conflicting institutional logics often prompt institutional hybridity, the paper conceptualizes and examines the role of three institutional logics present in research policy, namely academic excellence, utility of research, and funding efficiency. Using quantitative policy document analysis, a secondary literature review, and in-depth interviews, the paper reveals that, while a heated conflict existed between the proponents of the first two logics, the third was largely undisputed and, in fact, accommodated the final policy solution. The study’s results show that hybridity choices in Sweden can be linked to a combination of negotiations between vested interests, the state’s pursuit of better management and efficiency, strategic political action, and historical path dependency. Finally, this paper proposes several implications of segregation and other hybridity choices.